2017
DOI: 10.1021/acs.jpcc.7b03875
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Role of Metal–Oxygen Bond and O 2p Hole in High-Voltage Cathode LiNixMn2–xO4

Abstract: The role of transition-metal d and ligand p hybridization continues to be of immense interest in Li-ion battery cathode, and yet it is still poorly understood. Using combined experimental and theoretical soft X-ray absorption spectroscopic study and density functional theory calculation, we investigated the fundamental electronic structure of the high-voltage spinel LiNi x Mn2–x O4. An oxygen-participating charge rebalance between manganese and nickel ions was found; that is, the content of O 2p holes close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 55 publications
6
36
0
Order By: Relevance
“…The Fourier transforms of EXAFS (FT‐EXAFS) for Ni MOF NSs (Figure 4 d) showed a dominant peak appeared at ca. 1.6 Å belongs to the first shell coordination of Ni–O, and the typical Ni–Ni bond in the Ni foil was absent in Ni MOF NSs samples, [31, 32] The short Ni–O distance in Ni MOF NSs as shown in the Supporting Information, Table S4 as compared with that in NiO indicates high oxidation state of Ni ions in the former in line with the results from XANES and XPS. To further understand the origin of the different activities between the Ni MOF NSs samples, the coordination nature of their surface metal atoms was investigated.…”
Section: Figuresupporting
confidence: 77%
“…The Fourier transforms of EXAFS (FT‐EXAFS) for Ni MOF NSs (Figure 4 d) showed a dominant peak appeared at ca. 1.6 Å belongs to the first shell coordination of Ni–O, and the typical Ni–Ni bond in the Ni foil was absent in Ni MOF NSs samples, [31, 32] The short Ni–O distance in Ni MOF NSs as shown in the Supporting Information, Table S4 as compared with that in NiO indicates high oxidation state of Ni ions in the former in line with the results from XANES and XPS. To further understand the origin of the different activities between the Ni MOF NSs samples, the coordination nature of their surface metal atoms was investigated.…”
Section: Figuresupporting
confidence: 77%
“…Fast operando XAS analysis. Briefly, XANES provides reliable clues on an element's oxidation state 33,47 , while EXAFS conveys local structural information surrounding the absorbing atom 28,35,48 . Although finding out a novel catalyst is an interesting task, it is much more important to understand the mechanism and the formation process of active sites in catalysts during ECR.…”
Section: Resultsmentioning
confidence: 99%
“…[29,30] The XANES spectra indicated that the average valence state of Ni in the samples are larger than NiO reference (Figure 4 S3). The EXAFS wavelet transform (WT) analysis gives an intuitive way of further ascertaining the dispersion state of Ni atoms in the Ni MOF NSs through the comparison with reference samples (Figure 4 foil was absent in Ni MOF NSs samples, [31,32] The short Ni-O distance in Ni MOF NSs as shown in the Supporting Information, Table S4 as compared with that in NiO indicates high oxidation state of Ni ions in the former in line with the results from XANES and XPS. To further understand the origin of the different activities between the Ni MOF NSs samples, the coordination nature of their surface metal atoms was investigated.…”
mentioning
confidence: 99%